Ultrasound-triggered antibiotic release from PEEK clips to prevent spinal fusion infection: Initial evaluations. (15th July 2019) - Delaney, Lauren J.; MacDonald, Daniel; Leung, Jay; Fitzgerald, Keith; Sevit, Alex M.; Eisenbrey, John R.; Patel, Neil; Forsberg, Flemming; Kepler, Christopher K.; Fang, Taolin; Kurtz, Steven M.; Hickok, Noreen J.
Graphical abstract: Abstract: Despite aggressive peri-operative antibiotic treatments, up to 10% of patients undergoing instrumented spinal surgery develop an infection. Like most implant-associated infections, spinal infections persist through colonization and biofilm formation on spinal instrumentation, which can include metal screws and rods for fixation and an intervertebral cage commonly comprised of polyether ether ketone (PEEK). We have designed a PEEK antibiotic reservoir that would clip to the metal fixation rod and that would achieve slow antibiotic release over several days, followed by a bolus release of antibiotics triggered by ultrasound (US) rupture of a reservoir membrane. We have found using human physiological fluid (synovial fluid), that higher levels (100–500 μg) of vancomycin are required to achieve a marked reduction in adherent bacteria vs. that seen in the common bacterial medium, trypticase soy broth. To achieve these levels of release, we applied a polylactic acid coating to a porous PEEK puck, which exhibited both slow and US-triggered release. This design was further refined to a one-hole or two-hole cylindrical PEEK reservoir that can clip onto a spinal rod for clinical use. Short-term release of high levels of antibiotic (340 ± 168 μg), followed by US-triggered release was measured (7420 ± 2992 μg at 48 h). These levels are sufficient to prevent adhesion of Staphylococcus aureus to implant materials. This study demonstrates the feasibility of an US-mediated antibiotic delivery device, which could be a potent weapon against spinal surgical site infection. Statement of Significance: Spinal surgical sites are prone to bacterial colonization, due to presence of instrumentation, long surgical times, and the surgical creation of a dead space (≥5 cm 3 ) that is filled with wound exudate. Accordingly, it is critical that new approaches are developed to prevent bacterial colonization of spinal implants, especially as neither bulk release systems nor controlled release systems are available for the spine. This new device uses non-invasive ultrasound (US) to trigger bulk release of supra-therapeutic doses of antibiotics from materials commonly used in existing surgical implants. Thus, our new delivery system satisfies this critical need to eradicate surviving bacteria, prevent resistance, and markedly lower spinal infection rates.